Empowering leadership and innovative work behavior in start-up companies: Mediating role of proactive personality - Rifdah Hanandra; Pundani Eki Pratiwi (Humanitas: Indonesian Psychological Journal, 2025)
Today, some start-ups in Indonesia have failed in their development, one of the reasons is that they didn’t really present innovative solutions to answer society’s needs. Therefore, an appropriate innovation strategy is needed. This study aims to determine the influence of empowering leadership on innovative work behavior through the mediating role of proactive personality. This research used a quantitative approach with a cross-sectional survey design. The subjects in this study were 200 start-up employees in the Jabodetabek area with a purposive sampling technique, who are aged 20-40 years old, and minimum of one year of work experience. The research instruments used are Janssen’s Innovative Work Behavior Scale, Amundsen & Martinsen’s Empowering Leadership Scale, and Bateman & Crant’s Proactive Personality Scale. The analysis technique used is the Macro PROCESS by Hayes. The outcome demonstrates that the innovative work behavior of start-up employees in the Jabodetabek area is influenced by empowering leadership, which is also mediated by the employees' proactive personality. This research implies that leaders who apply empowering leadership provide more flexibility for employees, so they are likely to be more proactive, which can indirectly increase their innovative work behavior in carrying out work roles and tasks in the company.